Neorassismus in der Einwanderungsgesellschaft: Eine Herausforderung für die Bildung - Völkel, Bärbel; Pacyna, Tony (transcript, 2017)
Today's world is organized into nation-states. Postcolonial paradigms, nationalism, ethnocentrism and racism all form part of a nation that brings history, culture and identity into a broader context of meaning. This volume shows that the increasing cultural pluralization of societies necessitates an openness to encounters that ultimately change all involved. To experience this not as a loss, but rather as the beginning of something new, presents itself as the challenge of the future. The contributors, including Kien Nghi Ha, Ram Adhal Mall, Bea Lundt and Jörn Rösen, present analyses, interpretations and perspectives on what the first steps toward such a society might look like.